Crimes de perigo abstrato: um estudo à luz dos princípios da ofensividade e da precaução - Nemeti, Rogério (2015)
The aim with this study is to analyze the validity and legitimacy of the abstract danger s crimes to the principle of offensiveness or harmfulness. The problem that arises is the increasing adoption of this type of offense, with foundation in the principle of precaution, in order to control the call of Risk Society. Because, as know, in the abstract danger s crimes, it is not required the legal asset is exposed to risk, given that in such cases there is only a probability of placing the legal asset at risk. So, what we intend to discuss in this paper, it is whether this type of crimes offends the structure of the felony and the basic tenets of criminal law classic